Net primary production and soil respiration in New England hemlock forests affected by the hemlock woolly adelgid. Issue 8 (27th August 2014) - Finzi, Adrien C.; Raymer, Poliana C. L.; Giasson, Marc-André; Orwig, David A.
Abstract : The abundance of eastern hemlock ( Tsuga canadensis ) in eastern US forests has declined since the 1950s owing to the introduction of the non‐native insect, hemlock woolly adelgid (HWA, Adelges tsugae ). In southern New England, eastern hemlock is being replaced by the deciduous tree species, black birch ( Betula lenta ). To date there is little understanding of whether hemlock loss will fundamentally alter ecosystem C balance and component fluxes. In this study, we use a comparative approach to study potential changes in C fluxes and N cycling associated with HWA‐induced hemlock decline and replacement. The stands include primary‐ and secondary‐growth hemlock forests (>230 and 132 years old, respectively), recently disturbed stands (5 and 18 years old) that now have rapidly growing black birch saplings, and a mature black birch stand of age similar to the second‐growth hemlock stand. We found that aboveground net primary production was higher in the aggrading black birch stand and significantly so at 18‐years post‐HWA compared to the secondary‐hemlock stand it would likely replace. Rapid forest regrowth was accompanied by significantly higher rates of N uptake from the soil but also higher N‐use efficiency because most of the N taken up from the soil was allocated to the production of wood with a high C‐to‐N ratio. In contrast to patterns of aboveground production, the rate of soil respiration was lowest in the young stands and not significantly different from the second‐growth hemlock stand, suggesting little net effect of stand replacement on soil C efflux. The leaf litter decomposition study showed that black birch litter decomposed more rapidly than hemlock litter but that there was no effect of stand type on the rate of decomposition. Analyses of extracellular microbial exoenzyme activity painted a more nuanced pattern of variation among stands, with fine root biomass the only weakly explanatory variable. In combination with our prior work on C stocks, these results suggest that forests affected by HWA in southern New England will remain a sink for atmospheric CO2 despite reorganization of stand structure and species composition.